Comparative characteristics of preparations for temporary root canal filling in treatment apical periodontitis (Эндодонтия Today)
Apical periodontitis is an infectious disease caused by microorganisms colonizing the root canal system. For optimization of endodontic treatment, bacterial populations within the root canal should be eliminated or at least significantly reduced to levels where it is possible to recover the periapical tissues. This article discusses some aspects of bacterial persistence before and after the therapy, including the use efficiency of a new drug for the temporary filling of the root canal based on the data of microbiological studies.